2009
DOI: 10.3349/ymj.2009.50.5.683
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Physical Therapy and Physical Therapy Plus Calcitonin in the Treatment of Lumbar Spinal Stenosis

Abstract: Conservative treatment is effective in LSS patients with mild or occasionally moderate pain. 6 Daily life style adjustments, back training, exercise programs to stretch, strengthening the lumbar region, and general conditioning exercises both prescribed alone or together with physical therapy yield good clinical results. 8-10Original Article DOI 10.3349/ymj.2009.50.5.683 pISSN: 0513-5796, eISSN: 1976-2437 Yonsei Med J 50 (5) Purpose: The aim of our study was to compare the efficacy of physical therapy alone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Strengthening exercises were included in nine of the exercise intervention arms [10,25-28]. Specific details of these exercises were not included in any of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthening exercises were included in nine of the exercise intervention arms [10,25-28]. Specific details of these exercises were not included in any of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight separate instances from four studies reported an improvement (range 16-29%) in the first 3-months [24-26,28]. At 6-months, only one instance was reported (18%) [10], three at 12-months (13-20%) [10,25] and one at 24-months (16%) [10].…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that despite these promising results, in this study the definite effects of calcitonin on some of the significant confounding variables, including infrared heating, ultrasonic diathermy, and active lumbar exercises, are unclear. Sahin et al [ 10 ] randomized 45 patients between the intranasal calcitonin 200 U/day and paracetamol 1,500 mg/day treatment groups. Both groups received the same physical therapy including interferential current, hot pack, short wave diathermy, and exercise protocol.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible reasons for the difference observed between our study and those that used intranasal formulation of calcitonin may be the lower bioavailability of the nasal formulation of calcitonin in comparison to the intramuscular injection formulation (only around 3%, ranging from 0.3% to 30.6%) [ 12 ], and therefore when a lesser amount of calcitonin was absorbed into the systemic circulation, less benefits of calcitonin were observed. It should also be noted that although the studies conducted by Podichetty et al [ 11 ], Tafazal et al [ 12 ], and Sahin et al [ 10 ] were randomized control trials, it is not clear whether the randomization method was adequate or not; it is also not clear whether the treatment allocation was blinded or not. Therefore, these studies may have a potential bias and also a type II error, and thus, an insufficient sample size to detect the difference between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation